2014
DOI: 10.1089/cap.2013.0090
|View full text |Cite
|
Sign up to set email alerts
|

A 36 Month Naturalistic Retrospective Study of Clinic-Treated Youth with Attention-Deficit/Hyperactivity Disorder

Abstract: Within the first 6 months of visiting the hospital, >40% of the patients dropped out of treatment regardless of methylphenidate (MPH) use. Twenty percent of the subjects showed adherence to MPH medication after 36 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…Determining reasons why a higher percentage of Korean patients compared with the percentage of Asian patients in the main trial (n = 10; 5.1%) were lost to follow-up could shed light on why the aforementioned differences of the discontinuation rate in study results between the main trial and post hoc analysis occurred. Alternatively, although the discontinuation rate for the Korean subpopulation was higher than those of the Japanese and the Taiwanese subpopulations, Hong et al (2014) reported a comparable discontinuation rate among Korean pediatric patients with ADHD (42.4%) during the first 6 months after the treatment was initiated. It is possible that this same phenomenon might also occur in Korean adult patients.…”
Section: Discussionmentioning
confidence: 94%
“…Determining reasons why a higher percentage of Korean patients compared with the percentage of Asian patients in the main trial (n = 10; 5.1%) were lost to follow-up could shed light on why the aforementioned differences of the discontinuation rate in study results between the main trial and post hoc analysis occurred. Alternatively, although the discontinuation rate for the Korean subpopulation was higher than those of the Japanese and the Taiwanese subpopulations, Hong et al (2014) reported a comparable discontinuation rate among Korean pediatric patients with ADHD (42.4%) during the first 6 months after the treatment was initiated. It is possible that this same phenomenon might also occur in Korean adult patients.…”
Section: Discussionmentioning
confidence: 94%
“…It is controversial as to whether ADHD treatment can affect intelligence in adulthood, but a long-term study on natural progression in ADHD patients revealed that patients who were not treated during childhood showed a lower IQ in adulthood. 26) In an ADHD treatment compliance study, 14) children who terminated treatment early revealed that parents' education levels and the pediatric patients' IQ were higher compared to the group who maintained long-term treatment. That is, because pediatric patients with high intelligence discontinued treatment early, it is likely that the IQ of the CD in this study was lower than that of the AD.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated drug continuance according to the number of hospital visits. Considering the high treatment drop-out rate by the authors ( 18 ), the distribution of drop-out rates over 6 months for the treatment drop-out group was analyzed in 1-month units.…”
Section: Methodsmentioning
confidence: 99%
“…Although the results of previous studies differ, due to methodological differences, 3-year long-term drug compliance for pediatric ADHD patients is approximately 30% ( 11 - 16 ). In particular, there are large differences in the 6-month drop-out rate, at 20% ( 17 ), 42.4% ( 18 ), and more than 80% ( 19 ), depending on the drop-out criteria. Although the treatment discontinuance rate is high, it is also not true that all pediatric patients receive medicinal treatment after diagnosis of ADHD.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation